Realizing excellent energy storage performance and fatigue endurance in Sr0.7Sm0.2TiO3 modified 0.67BiFeO3-0.33BaTiO3 lead-free relaxor ceramics. Issue 16 (December 2022) - Liu, Shuo; Feng, Wuwei; Li, Jinhong; He, Bin; Liu, Meitang; Bao, Zhidi; Luo, Dengjie; Zhao, Changchun
Abstract: Environmentally friendly BiFeO3 -based capacitors have attracted great attention in energy storage applications. Herein, a large W rec of 2.91 J/cm 3 and a high η of 85% were obtained under the electric field of 220 kV/cm in (1-x)(0.67BiFeO3 -0.3 3BaTiO3 )-xSr0.7 Sm0.2 TiO3 (BF-BT-xSST) ceramics at x = 0.30. The addition of SST facilitates to enhance the relaxor behavior and suppress the early polarization saturation of ceramics. The breakdown strength of BF-BT-xSST ceramics is enhanced due to the significantly decreased grain size and the increased band gap. More importantly, the BF-BT-0.30SST ceramic exhibits an excellent fatigue endurance (< 1.1%, after 10 5 fatigue cycles), which is superior to most of previous works. In addition, BF-BT-0.30SST ceramic also shows high thermal and frequency stability, and fast discharge rate ( t 0.9 < 0.16 μs). We propose that the SST or a combination of SST and Sr0.7 Bi0.2 TiO3 is a better additive for the BF-based energy storage materials.